Evaluation of clinical efficacy and volumetric changes in pulpectomized primary molars: An invitro study - Tariq Akkam; Feras Masha; Mohammed Dhae; Abdulrahman Sherwani; Satish Vishwanathaiah; Ather Ahmed Syed (Elsevier, 2019)
Introduction: Pulpectomy is the intervention of choice for treating infected pulp tissue. Pulp therapy in primary teeth has been performed using various instrumentation techniques. However, the conventional instrumentation technique used for root canal preparation in primary teeth is hand instrumentation. Various Ni-Titanium instruments are available but are rarely used in primary teeth. Rotary instruments were introduced to pediatric endodontics by Barr et al in the year 2000. A new system Kedo S files has been introduced which has overcome the major disadvantages of using multifiles in pediatric population. Aims and objectives: To compare canal preparation between manual and rotary systems using CBCT and to compare volumetric filling using CBCT. Materials and Methods: A total of 30 extracted human primary teeth were included in the study. Teeth were cleaned and scaled and stored in 0.5% hypochlorite. Access cavity was done, pulp extirpated and irrigated with saline. The teeth were randomly divided into three groups. Group A, Group B and Group C. After canal preparation, root canal filling was done with Calcium hydroxide. The samples were subjected to CBCT analysis. Results: There was a significant difference in the volume of root canal enlarged in all the groups. Rotary files showed significant increase in the volume compared to K files.Rotary instrumented root canals showed good obturated volume compared to K files, although voids were common in all the groups. Conclusion: Rotary root canal instrumentation may be indicated for utilization in primary teeth, for enhancing root canal preparation and good quality of root canal filling.